PERLINDUNGAN HUKUM PEMEGANG SERTIFIKAT HAK GUNA USAHA AKIBAT KEKELIRUAN PENETAPAN BATAS TANAH - SHEILA NAMIRA (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhammad Yamin2. Budiman Ginting3. Saidin Dispute in land usually occurs in society, especially in land rights, such as errors in surveying land boundary which brings about overlapping land rights. Two land certificates of the same plot of land will cause legal uncertainty for their holders. The objective of the research was to find out the cause of errors in determining land boundary on leasehold certificate, legal consequence of error in determining land boundary, and legal protection for the holder of leasehold certificate caused by error in determining land boundary. The research used juridical normative and descriptive analytic methods. Primary data were gathered by conducting interviews in BPN (National Land Agency), secondary data were obtained from various literatures and legal provisions, and conclusion was drawn deductively.Keywords: Legal Protection, Certificate, Error in Determining Boundary